Developing Mindful Leadership among Learners - Wendy Griswold (Adult Education Research Conference, 2017)
This roundtable presents preliminary findings from a study on teaching mindfulness skills to adults seeking to acquire leadership skills. Impact on participant learning in terms of both course content and self-discovery will be evaluated.
Keywords: contemplative pedagogy; mindfulness; leadership